Exposure to chemical pollutants and biological aerosol in indoor facilities for recreational and sport horses - Izabela Rodzyń; Katarzyna Karpińska; Hanna Bis-Wencel; Łukasz Wlazło; Mateusz Ossowski; Katarzyna Strzelec; Sebastian Jaguszewski; Bożena Nowakowicz-Dębek (BMC Veterinary Research, 2024)
Abstract Background Due to the increasing prevalence of equine non-infectious respiratory disease, the air contamination in equine housing (Stables A-C) and training facilities (indoor riding arenas A - C) was investigated. The aim of the study was to monitor gaseous pollutants, bioaerosols, and dust concentrations at three different sites (stables and riding halls), where different floor materials were used in the riding halls. Materials and methods Air quality was monitored in housing for horses and in riding halls in terms of dust concentration, the presence of gaseous chemical pollutants, and concentrations of biological aerosol. Statistical analysis was performed using analysis of variance (ANOVA). The levels obtained were compared with acceptable limits. Results Among the gaseous pollutants identified, the highest concentration was obtained for ammonia in stables B and C (16.37 and 22.39 mg/m3, respectively). Standards for total dust were exceeded in stables B and C and in riding halls B and C. The highest numbers of bacteria and fungi were recorded in stables A and C and in riding hall B. Ulocladium sp. had the highest percentage share among the moulds identified. Conclusions The results confirm that the wrong choice of bedding in the stable and indoor riding arenas may contribute, even in short training periods, to equine non-infectious respiratory disease (equine asthma). Bioaerosol suspended in the air together with released gaseous pollutants can exacerbate this phenomenon, which even in the case of short training periods can lead to equine asthma of varying degrees of severity. For this reason, the choice of floor material in riding halls should be treated as a priority, as the wrong decision can shorten the period during which the horse can be used for recreational purposes.